CCR2 mediates Helicobacter pylori‐induced immune tolerance and contributes to mucosal homeostasis. Issue 2 (8th December 2016) - Sun, Xia; Zhang, Min; El‐Zaatari, Mohamad; Huffnagle, Gray B.; Kao, John Y.
Abstract: Background: We previously demonstrated that H. pylori infection leads to increased induction of regulatory T cells in local and systemic immune compartments. Here, we investigate the role of CCR2 in the tolerogenic programing of dendritic cells in a mouse model of H. pylori infection. Materials and Methods: CCR2 deficient (CCR2KO) mice and wild‐type (Wt) mice infected with H. pylori SS1 strain were analyzed by qPCR and FACS analysis. In vitro, bone marrow‐derived DC on day 6 from CCR2KO and Wt mice cocultured with or without H. pylori were examined to determine the impact of CCR2 signaling on dendritic cells function by qPCR, ELISA, and FACS analyses. Results: Acute H. pylori infection was associated with a threefold increase in CCR2 mRNA expression in the gastric mucosa. H. pylori ‐infected CCR2KO mice exhibited a higher degree of mucosal inflammation, that is, increased gastritis scores and pro‐inflammatory cytokine mRNA levels, but lower degree of H. pylori gastric colonization compared to infected Wt mice. Peripheral H. pylori ‐specific immune response measured in the CCR2KO spleen was characterized by a higher Th17 response and a lower Treg response. In vitro, CCR2KO bone marrow‐derived DC was less mature and shown a lower Treg/Th17 ratio. Moreover, blockade of CCR2 signaling by MCP‐1 neutralizing antibody inhibited H. pylori ‐stimulated bone marrow‐derived DC maturation. Conclusions: Our results indicate that CCR2 plays an essential role in H. pylori ‐induced immune tolerance and shed light on a novel mechanism of CCR2‐dependent DC Treg induction, which appears to be important in maintaining mucosal homeostasis during H. pylori infection.